A Modular Approach for Diversity‐Oriented Synthesis of 1, 3‐trans‐Disubstituted Tetrahydroisoquinolines: Seven‐Step Asymmetric Synthesis of Michellamines B and C. Issue 31 (17th June 2022) - Bai, Miao; Jia, Shihu; Zhang, Jingyang; Cheng, Hong‐Gang; Cong, Hengjiang; Liu, Shanshan; Huang, Zhiqian; Huang, Yaoguo; Chen, Xiaoming; Zhou, Qianghui
Abstract: 1, 3‐ trans ‐Disubstituted tetrahydroisoquinoline (THIQ) is a common heterocyclic structural unit of naphthylisoquinoline alkaloids. The assembly of this structural unit is not trivial, which constitutes a substantial challenge in the total synthesis of naphthylisoquinoline alkaloids and related pharmaceuticals. Herein, we report a modular and convergent method for the rapid assembly of 1, 3‐ trans ‐disubstituted THIQ frameworks through a three‐component Catellani reaction and a Au I ‐catalyzed cyclization/reduction cascade. With widely available simple aryl iodides, aziridines and (triisopropylsilyl)acetylene as the building blocks, this method paves a practical way for the diversity‐oriented synthesis of 1, 3‐ trans ‐disubstituted THIQs. Based on this new method, concise syntheses of an analogue of the new drug mevidalen and four naphthylisoquinoline alkaloids have been accomplished, demonstrating the broad synthetic utility of this approach. Abstract : A modular and step‐economical approach based on a three‐component Catellani reaction and a gold(I)‐catalyzed cyclization/reduction cascade has been established for the diversity‐oriented synthesis of 1, 3‐ trans ‐disubstituted tetrahydroisoquinolines. This synthetic strategy enabled concise syntheses of an analogue of the new drug mevidalen as well as four naphthylisoquinoline alkaloids.